STRATEGI PENYULUH AGAMA ISLAM DALAM MEMINIMALISIR BUTA AKSARA AL-QUR’AN DI MAJELIS TAKLIM HIDAYATUSSIBYAN - Siti Khowajah; Depi Putri; Novita Sari; Agussalim Agussalim (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi Islam Institut Agama Islam (IAI) Al-Azhaar Lubuklinggau, 2025)
Quran illiteracy has been problem in the Hidayatussibyan Taklim Assembly, Sadarkarya Village, Purwodadi District, Musi Rawas Regency. Based on data from the South Sumatera BPS 2022, it was recorded that 2.58% of the people in Musi Rawas Regency were illiterate in the Quran. Of the 30 congregation members, 50% were still at the 1-6 volume stage, and 50% had read the Quran. This study used a descriptive qualitative method with a case study approach. Data collection techniques included interviews, observations, and documentation. Counseling was carried out through activities reading the Quran, learning ablution, dhuha prayer, and tahlil, with material according to tajwid using the Iqro' method. The strategies implemented include: (1) grouping the congregation based on ability; (2) special guidance outside of routine religious studies; (3) providing learning materials such as Iqro', Juz Amma, and the Quran; (4) training in reading and writing the hijaiyah letters; and (5) a personal approach to building motivation. This strategy is effective in improving the ability to read the Qur'an and reducing the level of illiteracy among the congregation